Experimental investigation on the use of reduced graphene oxide and its hybrid complexes in improving closed conduit turbulent forced convective heat transfer - Zubir, M.N.M.; Badarudin, A.; Kazi, S.N.; Huang, N.M.; Misran, M.; Sadeghinezhad, E.; Mehrali, M.; Syuhada, N.I.; Gharehkhani, S. (Elsevier, 2015)
The present research highlighted on the use of Reduced Graphene Oxide (RGO) and its hybrid complexes in an effort to improve the convective heat transfer performance in closed conduit configuration. The RGO was synthesized via the reduction process of chemically exfoliated Graphene Oxide (GO) using Tannic Acid (TA) as reductant. Different amount of pristine carbon sources (i.e. Multiwall Carbon Nanotube (MWCNT), Carbon Nanofiber (CNF) and Graphene nanoPlatelets (GnP)) was allowed to interact with RGO to form a hybrid complexes aiming to explore the capability of the mixtures to promote heat transfer process. It was discovered that the trend of results appeared to coincide to the previous documented findings on heat transfer enhancement related to the addition of graphene based materials. Further, the enhancement of heat transfer coefficient was beyond the increase in thermal conductivity alone which suggested prominent contribution from both the particle and turbulent induced flow characteristics. The enhancement was more pronounced at the entrance of the heating section as well as at high Reynolds number (Re), paving opportunities for further investigation to gain in-depth understanding on the mechanisms involved. As high as 144% enhancement in Nu was recorded near the conduit entrance and about 63% at the downstream section. Studies on hydrodynamic parameters indicated negligible increase in pressure loss as well as friction factor for RGO and its hybrid mixtures, indicating the potential use of RGO as favorable additives in addressing the persistent limitation of conventional heat transfer liquid within the perspective of convective heat transport system.